Investigation of Processes in the Traction Capacitor Circuit of the Model of High-Speed Magnetolevitation Transport - Holota, O. O.; Mukha, A. M.; Ustymenko, D. V.; Plaksin, S. V. (Science and Transport Progress, 2024)
Purpose. High-speed magnetolevitation transport (maglev), based on the principle of electrodynamic suspension, has features in the form of large sections of the windings of the track coils. Therefore, there is a need to study electrical processes in the circuits of these coils to improve the efficiency of the energy performance of this type of transport. The study of electrical processes in the circuits of a track power plant makes it possible to substantiate the prerequisites for the creation of a distributed energy storage and transmission system. The power plant consists of separate subsystems, including a primary energy storage unit, an energy distribution unit, and a traction module. The main purpose of this study is to determine the nature of transients in the energy distribution unit and to obtain the characteristics of the traction capacitor discharge process. Methodology. We modeled an electrical circuit that would meet the needs of the corresponding energy distribution unit of the track structure for the required operating conditions of the maglev motion system – control pulses with different combinatorics. In the course of the study, computer modeling of physical systems in the Scilab software environment was used. Findings. A review of existing studies has been carried out and the relevance of the study of the track power plant for high-speed magnetolevitation transport has been substantiated. The basic mathematical dependences of electrical circuits with capacitive and inductive elements are given. A structural representation of the inductive section of the maglev motion system with a traction module is created: traction coils and a capacitor, as well as a converter-pulse signal unit. An effective tool for analyzing transient processes has been created. Originality. For the first time, the structural and elemental realization of the power distribution unit for the road power plant of high-speed land transport is proposed. The time dependencies describing the processes in the proposed system during the implementation of the principles of pulse control of traction coils are obtained. Based on the analysis of the nature of transients in the traction capacitor circuit, the directions of further development of this power plant are proposed. Practical value. The results of the work create the basis for further research and development of experimental research models (test bench) of the maglev in order to obtain new ratios and characteristics that will confirm the effectiveness and efficiency of the new control principle of the proposed system.